ВИЗНАЧЕННЯ ПАРАМЕТРІВ РЕГУЛЯТОРА В СИСТЕМІ КЕРУВАННЯ DC/DC ПЕРЕТВОРЮВАЧЕМ З КВАЗІ-ІМПЕДАНСНОЮ ЛАНКОЮ ЗА УМОВИ СТІЙКОСТІ ДЛЯ МАЛОГО СИГНАЛУ - Гусев , О.О. (Інститут електродинаміки НАН України, Київ, 2013)
Peculiarities of DC/DC converters based on the qZS-network were considered. Control system of the converter is described. By means of small signal model of transfer function the stability analyzes was performed. The results of the analytical analysis and experimental investigation showed that a DC/DC converter based on the qZS-network has limited but predictable stability margin. The area of coefficients of PI-regulator in which the system is stable was found. It was shown that stability margin depends on coefficients of PI-regulator and operation point of the converter. References 7, table 1, figures 5.